Redemption of Shares or Stocks and Their Influence on Tax Obligation in Value Added Tax - Jakub Piętka (Przegląd Prawno-Ekonomiczny)
The article presents the problem of taxation of value added tax and the remuneration in kind paid to a shareholder as a result of the redemption of shares. Settlements made between a company and a former shareholder may be considered a taxable transaction. Two opposing concepts found in the case law are to treat for tax purposes the redemption of shares with remuneration as a single transaction, or to separate only the phase of payment of remuneration for the redeemed shares and consider it a supply of goods for consideration. The practical importance of the issues raised is evidenced by the fact that these settlements often result in significant property flows. The purpose of the article is to try to demonstrate which of the existing concepts corresponds to the provisions of the law and the structural principles of the value added tax more closely.